EFEKTIFITAS PELATIHAN PENGENALAN DIRI TERHADAP PENINGKATAN PENERIMAAN DIRI DAN HARGA DIRI - Handayani, Muryantinah Mulyo; Ratnawati, Sofia; Helmi, Avin Fadilla (Jurnal Psikologi, 1998)
The present research, based on Johary window’s concept, was designed to test the hypothesis that self-knowledge training effective to the increased self-acceptance and self-esteem score’s subjects.The research design was pre-test post-test control group design. Thirty-four subjects participated and divided into two group, one experiment group and one control group. The groups filled out 2 scales, self-acceptance and self-esteem scales before (pre-test) and after (post-test) training. Result showed that self-acceptance and self-esteem scores of subjects in the experiment group are higher than the control group. The self-knowledge training effectively increased self-acceptance and self-esteem subjects.